Efeitos do treinamento do método Pilates na modulação autonômica da frequência cardíaca e na composição corporal: um ensaio clínico randomizado e uma revisão sistemática com meta-análise - Cavina, Allysiê Priscilla de Souza [UNESP] (2019)
The objective of the present dissertation was to verify the effect of the training of the Pilates method on the autonomic modulation of heart rate, besides presenting a systematic review with meta-analysis on the effectiveness of the Pilates method in body composition. Methods: The clinical trial consisted of 47 healthy men aged 18 to 35 years were analyzed. Participants were divided into two groups: Pilates group (GP) and control group (CG). The GP performed 36 sessions of the Pilates method for approximately 60 minutes each session and often three times a week. For the Systematic Review, the studies were selected using seven databases (MEDLINE, EMBASE, SportDiscus, PEDro, SciELO, CINAHAL and The Cochrane Library), from the oldest record of each database until the 28th of March of 2018. Results: In the clinical trial, there was an interaction of moments versus groups for the GP in the SDNN indices (p = 0.021), LF [ms2] (p = 0.016) and SD2 (p = 0.011) in addition, there was a statistically significant (p <0.05) increase in GP delta values when compared to CG for the overall HRV indices. Twelve eligible studies were chosen for the systematic review. The main findings of this review were that, when analyzed without distinction of population, the Pilates method was more effective than the conditions of comparison only for abdominal circumference (seven studies, n = 295; SMD = 0.24, 95% CI , 01, 0.48], p = 0.04, I 2 = 0%,). In the exploratory analysis for the elderly population, it was observed that the Pilates method had a significant effect on abdominal circumference (three studies, n = 130; SMD = 0.37, 95% CI [0.02, 0.72]; p = 0.04, I 2 = 0%). For the other analyzes, no significant differences were observed. Overall conclusion: Pilates training can promote changes in the autonomic modulation of the HR, characterized by significant gains in overall variability, in addition to the Pilates method being better than the conditions of comparison in the reduction of waist circumference.